Optimization of maltodextrin coating for masking to maintain the characteristic of Spirulina powder using the Box-Behnken design: A Response Surface Methodology approach - Prasetiyo Himawan; Purwaningsih Sri; Setyaningsih Iriani; Sadi Uju; Nurilmala Mala; Tarman Kustiyariyah (BIO Web of Conferences)
Masking or encapsulating spirulina has been widely used to overcome unpleasant flavours and aromas. Masking procedures, including rehydration, mixing, and heating, might impact the characteristic of spirulina powder. This study aimed to identify the relationship between variables spirulina masking using maltodextrin and develop the model to optimize the response. Response Surface Methodology (RSM) and Box-Behnken Design (BBD) was employed to evaluate optimum conditions for spirulina masking. The masking variables, such as heating temperature, heating period, concentration of maltodextrin and ratio of maltodextrin and spirulina, were studied extensively. Masking process was evaluated based on colour changes (ΔE), moisture, and crude phycocyanin content (CPC) responses. The results showed a moderate positive relationship between the masking variables, with a coefficient of determination (R2) value between 0.3-0.7. The response analysis showed a non-significant lack of fit (p>0.05), indicating that the data response will match with the optimized prediction model. The optimized conditions of spirulina masking were determined in low-temperature heating at 33°C for 60 min, with 7 g/L maltodextrin concentration and a 1:1 ratio of spirulina and maltodextrin (m/v). The optimized masking process condition could reach responses, moisture of 7.23 %, ΔE of 1.68, and CPC of 6.71 mg/g, respectively.